Efficacy and safety of new direct antiviral agents in hepatitis C virus–infected patients with diffuse large B‐cell non‐Hodgkin's lymphoma. Issue 1 (24th November 2017) - Persico, Marcello; Aglitti, Andrea; Caruso, Rosa; De Renzo, Amalia; Selleri, Carmine; Califano, Catello; Abenavoli, Ludovico; Federico, Alessandro; Masarone, Mario
Abstract : The association of hepatitis C virus (HCV) with non‐Hodgkin's lymphoma (NHL) has been demonstrated throughout the world. The new interferon‐free direct antiviral agents (DAAs) showed high efficacy and safety, and preliminary data seem to confirm their activity on low‐grade NHL. The question arises as whether or not—and how—to treat the HCV‐positive patients suffering from diffuse large B‐cell lymphomas (DLBCLs). The aim of this observational study was to evaluate whether DAA antiviral treatment of DLBCL/HCV‐infected patients in concomitance with chemotherapy is a safe and effective option. Twenty (13 males and 7 females) HCV genotype 1b‐positive subjects, undergoing chemotherapy for DLBCL, were enrolled between June 2015 and December 2015. After informed consent, all patients underwent antiviral therapy (AVT) with sofosbuvir/ledipasvir and chemotherapy (14 rituximab plus cyclophosphamide, doxorubicin, vincristine, and prednisone and 6 cyclophosphamide, doxorubicin, vincristine, and prednisone) for DLBCL. Complete hematological (Revised European‐American Lymphoma classification, Ann Arbor, and International Prognostic Index [IPI] scores) and hepatological (viral markers, liver stiffness, and biochemical parameters) evaluations were made. A historical retrospective cohort of 101 DLBCL/HCV‐positive patients not undergoing AVT was enrolled for comparison. DAA‐ treated and untreated patients were similar for sex distribution, IPI score, and NHL stage, and differed for age (older in treated), chemotherapy and use of AVT. Overall survival (OS) and disease‐free survival (DFS) were evaluated among a 52‐week of follow‐up. No statistical difference was found in OS after 52 weeks ( P = 0.122), whereas a statistically significant higher DFS was achieved in treated patients ( P = 0.036). At the multivariate analysis, only IPI score and AVT were independently correlated with a better DFS. No differences in adverse events were reported. Conclusion: DAA treatment in concomitance with chemotherapy was shown to be safe and effective in influencing remission of aggressive lymphomas in HCV patients. (Hepatology 2018;67:48‐55).